Effect of Slow Deep Breathing on Lung Function Among Individuals with Multi-Drug-Resistant Tuberculosis (MDR-TB) at a Regional General Hospital in Indonesia - Nur Hafizah; Widiharti Widiharti; Widya Lita Fitrianur; Ernawati Ernawati (Fundamental and Management Nursing Journal)
Introduction: Multi Drug Resistant Tuberculosis (MDR-TB) sufferers experience decreased lung function. Non-pharmacological therapy such as slow deep breathing has been widely applied to improve lung function of individuals with Tuberculosis. However, the results were inconsistant. The aim of this research is to analyze the effect of slow deep breathing on lung function pf individuals with multi-drug resistant (MDR-TB) at the MDR-TB Polyclinic Ibnu Sina General Hospital Gresik, Indonesia.